Illiberal Peacebuilding dan Ekstraktivisme di Indonesia: Studi Manajemen Konflik Autoritarian terhadap Konflik Sumber Daya Alam tahun 2018-2022 - Jasmine Rafifah Fathia Putri; Adhi Cahya Fahadayna (Jurnal Ilmu Sosial dan Ilmu Politik)
The distribution of natural resource utilization is often exploited by certain parties, where not all elements of society can enjoy the economic benefits from Indonesia's natural wealth. This study aims to analyze the influence of patronage practices on resource conflicts in Indonesia using the theoretical framework of Authoritarian Conflict Management (ACM) and land politics. The research employs a quantitative method based on secondary data obtained from the V-Dem and SNPK Indonesia databases. The independent variables in this study include discursive practices, spatial practices, and political-economic practices, while the dependent variable is the resource conflict index. Data analysis was conducted using multiple linear regression techniques with the SPSS software version 26 to ensure data validity and reliability. The results indicate that, overall, the relationship between the independent and dependent variables is statistically insignificant. This finding suggests that the Authoritarian Conflict Management theory may not be universally applicable, especially in Indonesia, which exhibits complex and diverse socio-economic and political dynamics. This study underscores the importance of considering regional factors and local characteristics in understanding resource conflicts in Indonesia.